(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
Baccaurea lanceolata (Miq.) Müll.Arg., native to Southeast Asia, is valued in traditional practices and local diets for its potential medicinal properties. However, the biological activities of its fruit vinegar remain underexplored. This study aimed to optimise and evaluate the antioxidant and antimicrobial properties of B. lanceolata fruit vinegar (BLFV). A central composite design was applied to optimise fermentation time (FT), sugar concentration (SC), and solid-to-liquid ratio (SLR) as component variables, with total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity via the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay as response variables. The antimicrobial activity of the optimised BLFV was assessed against Gram-positive (Enterococcus faecalis and Staphylococcus aureus) and Gram-negative (Acinetobacter baumannii and Klebsiella pneumoniae) bacteria using the disc diffusion method. The optimised BLFV process, using a 2-month FT, 20% SC, and 1:2 g/mL SLR, achieved the following response factors: 438.070 ± 0.130 mg GAE/L vinegar (TPC), 10.466 ± 0.130 mg CE/L vinegar (TFC), and 83.212 ± 0.130% (DPPH). Additionally, the optimised BLFV exhibited antimicrobial activity with inhibition zones measuring 8.03 ± 0.01 mm (E. faecalis), 9.06 ± 0.04 mm (S. aureus), 7.06 mm ± 0.01 (A. baumannii), and 7.20 ± 0.01 mm (K. pneumoniae). This study successfully optimised the BLFV process, highlighting its antioxidant and antimicrobial properties, which hold promise for applications in developing nutraceuticals and functional foods.